Oxidative Stress in Depression: The Link with the Stress Response, Neuroinflammation, Serotonin, Neurogenesis and Synaptic Plasticity - Ana Salomé Correia; Armando Cardoso; Nuno Vale (MDPI AG, 2023)
Depression is a prevalent, complex, and highly debilitating disease. The full comprehension of this disease is still a global challenge. Indeed, relapse, recurrency, and therapeutic resistance are serious challenges in the fight against depression. Nevertheless, abnormal functioning of the stress response, inflammatory processes, neurotransmission, neurogenesis, and synaptic plasticity are known to underlie the pathophysiology of this mental disorder. The role of oxidative stress in disease and, particularly, in depression is widely recognized, being important for both its onset and development. Indeed, excessive generation of reactive oxygen species and lack of efficient antioxidant response trigger processes such as inflammation, neurodegeneration, and neuronal death. Keeping in mind the importance of a detailed study about cellular and molecular mechanisms that are present in depression, this review focuses on the link between oxidative stress and the stress response, neuroinflammation, serotonergic pathways, neurogenesis, and synaptic plasticity's imbalances present in depression. The study of these mechanisms is important to lead to a new era of treatment and knowledge about this highly complex disease.